Caregiver and divine support: Associations with resilience among adolescents following disclosure of sexual abuse. (November 2020) - Gower, Tricia; Rancher, Caitlin; Campbell, Jeanine; Mahoney, Annette; Jackson, Mindy; McDonald, Renee; Jouriles, Ernest N.
Abstract: Background: Social support is believed to be important for fostering adolescent resilience following sexual abuse. Caregiver support is often examined as a source of support for adolescents, but divine support (support from God or a higher power) has received scant research attention. Objective: This study examines relations of caregiver support and divine support with resilience following adolescent sexual abuse. Participants and Setting: Participants were 548 adolescents aged 11–17 ( M age  = 13.78; 91% female) and their non-offending caregivers ( M age  = 39.68; 79% mothers). Families were recruited from a children's advocacy center located in the southern United States following a disclosure of sexual abuse. Methods: Adolescents completed measures of caregiver and divine support and their social and academic functioning; caregivers and adolescents reported on adolescent psychological functioning. Resilience was operationalized as the absence of clinical levels of psychological symptoms together with the presence of adaptive levels of social and academic functioning. Results: Both caregiver support ( r = .19, p  < .001) and divine support ( r = .14, p  = .001) were positively associated with resilience. Considered together in regression analyses, caregiver support (OR = 1.02, p  = .001) and divine support (OR = 1.06, p  = .04) were both associated with resilience. Conclusion: Clinicians and researchers should consider the potential contribution of caregiver and divine support to adolescent resilience following sexual abuse.